Pengaruh penggunaan tepung limbah udang fermentasi terhadap karakteristik organ reproduksi pada puyuh petelur (Coturnix coturnix japonica) - Hilkias, Welda; Suprijatna, Edjeng; Ondho, Yon Soepri (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
The aim of the present study was to evaluate the effect of fermented shrimp waste meal on the characteristics of reproductive organs such as live weight, oviduct weight and length, ovarian weight, total yellow follicles, total white follicles, oviduct percentage and reproductive organ percentage. This experiment was conducted on Faculty of Animal Science and Agriculture, Diponegoro University. A total of 250, 6-week-old Japanese quail (consist of 250 females) were randomly assigned to one of 5 dietary treatments. 1st group (T0) was fed by diet without shrimp waste (control), 2nd group (T1) was fed by diet with 7,5% non-fermented shrimp waste, 3rd group (T3) was fed by diet with 5% fermented shrimp waste (FSW), 4th group (T3) was fed by diet with 7,5% FSW and 5th group was fed by diet with 10% FSW. 2 quails from each replicates were taken as samples. The members of a given sample were killed by severing the neck then separated the reproductive organs from the body. Measured the live weight, oviduct weight and length, ovarian weight, total yellow follicles, total white follicles, oviduct percentage and reproductive organ percentage. All data were examined using analysis of variance (ANOVA). The results showed that the effect of fermented shrimp waste meal on reproductive organs characteristics such as live weight, oviduct weight and length, ovarian weight, total yellow follicles, total white follicles, oviduct percentage and reproductive organ percentage were not significant. The use of fermented shrimp waste up to 10% didn’t obstruct the growth and development of quail reproductive organs.